2022
DOI: 10.1097/md.0000000000032053
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of extracorporeal shock wave on low back pain: A systematic review and meta-analysis

Abstract: Background: Extracorporeal shock wave therapy (ESWT) is a relatively new type of treatment for many musculoskeletal disorders. However, ESWT for low back pain remains controversial as the pain relieve benefit is questionable. We performed this systematic review and meta-analysis to explore the effectiveness and safety of ESWT interventions on pain and disability in patients with low back pain (LBP). Methods: In this meta-analysis, we searched electronic databases in the Pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…The 22 [9–30] studies comprised 13 [9–11,14,17,20,24–30] in Chinese and 9 in English, 20 [1–13,15–26,28–35] were journal articles, 2 [14,27] were master’s theses, and 1749 patients were involved, with 881 and 868 patients in the experimental and control groups, respectively. Twenty-two studies were RCTs, all of which stated that “there was no statistically significant difference between the baseline of the experimental group and control group ( P > .05).” Table 1 presents the baseline characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The 22 [9–30] studies comprised 13 [9–11,14,17,20,24–30] in Chinese and 9 in English, 20 [1–13,15–26,28–35] were journal articles, 2 [14,27] were master’s theses, and 1749 patients were involved, with 881 and 868 patients in the experimental and control groups, respectively. Twenty-two studies were RCTs, all of which stated that “there was no statistically significant difference between the baseline of the experimental group and control group ( P > .05).” Table 1 presents the baseline characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Ma [ 8 ] meta-analysis, which was not prospectively registered and included only 5 randomized controlled trials, concluded that more evidence for the safety of ESWT is needed, and the parameters of ESWT require further investigation, short-term efficacy of ESWT was superior to that of the control group, but the long-term efficacy was unclear. Li [ 7 ] meta-analysis had some errors in the characteristic table of the included studies: in Eftekharsadat [ 12 ] trial, patients in the control group received trigger point injection combined with kinesitherapy, but Li reported it as a sham ESWT; magneto-thermo-vibration therapy in Zheng [ 28 ] study was also reported as a sham ESWT. The findings of Liu [ 6 ] meta-analysis, which included only English literature, revealed that ESWT had both short-term and long-term efficacy; this study assessed mental health for the first time, but the difference was not significant; the grouping in subgroup analysis was not thorough, in Taheri [ 22 ] trial, the observation group received ESWT combined with kinesitherapy, while the control group received sham ESWT combined with kinesitherapy, both groups received same oral drugs, but Liu briefly defined it as ESWT versus oral medication and conducted a subgroup analysis based on it.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations